Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kepatuhan Kerja terhadap Kinerja Karyawan di CV Multe TC, Kota Kediri - Fadilah Salsabila; Mahyudi , Beny (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work motivation, work discipline, and work compliance on employee performance at CV. Multec TC using a quantitative approach. Data was collected through questionnaires distributed to 78 respondents and analyzed using SPSS. The findings show that all three variables have a positive and significant partial effect on employee performance. Work motivation has a significance value of 0.004, while work discipline and work compliance show stronger significance values of 0.000. These results indicate that employee performance is improved through motivation, discipline, and adherence to rules, providing a basis for management to formulate performance-enhancing policies. Keywords: Motivation; Discipline; Work Compliance; Employee Performance